Creole portraits of France's foreign relations during the long nineteenth century - Grigsby, Darcy Grimaldo (The Pennsylvania State University Press, 2022)
"Examines visual representations of and by persons defined as Creole, the term applied to white, Black, and mixed-race persons born in French colonies during the nineteenth century"--